All-or-nothing oblivious transfer based on the quantum one-way function - Wang, Ping; Su, Yiting; Sun, Zhiwei (Frontiers in Physics, 2022)
Oblivious transfer (OT) is one of the keystones of secure multi-party computation. It is generally believed that unconditionally secure OT is impossible. In this paper, we propose a practical secure quantum all-or-nothing oblivious transfer protocol based on the quantum one-way function. The protocol is built upon a quantum public-key encryption construction and its security relies on the no-cloning theorem and no-communication theorem. Practical security is reflected in limitations on non-demolition measurements.